INSISTS VS Islam Liberal 2003-2012: Corak Baru Argumentasi Islam di Indonesia : Islamic Intellectual Debates in Indonesia, 2003–2012: INSISTS vs. Liberal Islam - Tiar Anwar Bachtiar (TSAQAFAH, 2025)
This research analyzes the intellectual debate between INSISTS and Liberal Islam in Indonesia during 2003–2012 from the perspective of Islamic civilizational studies. Using a historical method—heuristic, critical, interpretative, and historiographical—combined with a narrative approach, the study situates INSISTS within a broader civilizational discourse on knowledge, authority, and modernity. The findings indicate that INSISTS adopts an academically grounded strategy in engaging Liberal Islamic arguments, differentiating itself from earlier movements that relied more on social or political mobilization. The wide influence of INSISTS arises from the scholarly prestige of its members and its ability to connect with long-established Islamic institutions such as Gontor, MUI, NU, Muhammadiyah, Persis, and DDII. This article argues that the INSISTS–Liberal Islam debate reflects deeper civilizational tensions within Indonesia’s Islamic thought regarding epistemology, modernization, and the negotiation of global ideas.